PENGARUH KETERLIBATAN KERJA DAN DUKUNGAN ORGANISASI TERHADAP PERILAKU KERJA INOVATIF PADA KARYAWAN GEN Z DENGAN KEPUASAN KERJA SEBAGAI VARIABEL MEDIASI: STUDI PADA KARYAWAN USAHA CAKE DI KOTA PALANGKA RAYA - Afrida Purba, Ella; Retawati, Anike; Hamzah, Pratiwi; Giovanni, Jonathan (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
This study aims to analyze The Influence of Work Engagement and Organizational Support on Innovative Work Behavior Among Gen Z Employees, With Job Satisfaction as A Mediating Variable (A Study of Cake Business Employees in Palangka Raya). The background of this study stems from the decline in innovation among Gen Z employees, even though this generation is known for its creativity, which is currently emerging in the world of work, especially in the culinary business. This study uses a quantitative approach with partial least square (PLS) analysis techniques. The population in this study consisted of 75 Gen Z employees working in cake shops in Palangka Raya City. The sampling technique used purposive sampling. The results of the study indicate that work engagement and organizational support have a positive and significant effect on employees' innovative work behavior. Additionally, job satisfaction also has a significant effect on innovative work behavior and mediates the relationship between work engagement and organizational support toward innovative work behavior.